Violence in a Changing Political Context: Northern Ireland and South Africa - Knox, Colin; Monaghan, Rachel (My University, 2003)
Northern Ireland and South Africa are moving from conflict to post-conflict societies. Both countries have new political dispensations and seek to eschew the legacy of bitter and bloody violence. The history of the political struggles has, however, embedded a culture tolerant of violence characterised by descriptions such as ‘an acceptable level of violence’ or ‘an imperfect peace’. Somehow the threshold of violence is different/higher in these countries because of their transitional status. This chapter will therefore explore how the meaning of violence is inextricably linked to the political context in Northern Ireland and South Africa. Specifically it will examine the continuing role of violence meted out by paramilitary/vigilante groups to alleged wrongdoers within the communities in which they operate, the stranglehold these groups exert and how, if at all, this is changing. The role played by the police and the criminal justice systems will also be discussed within the new era of established political systems that have replaced ‘white rule’ and ‘direct rule’ in South Africa and Northern Ireland respectively.
Keywords: Northern Ireland; South Africa; Violence; Politics